The Merits and Demerits of Undergraduate Exit Exams: A Systematic Literature Review - Samson Worku Teshome (Indonesian Journal of Innovative Teaching and Learning, 2025)
Background: Exit exams in higher education serve as a critical mechanism for assessing students' readiness for professional or advanced academic pursuits. These high-stakes assessments are intended to uphold academic and professional standards, promote accountability, and ensure quality across institutions. Objective: This study aims to systematically review the existing literature to evaluate the benefits and challenges of exit exams in higher education, focusing on their effectiveness, equity, and implications for students and institutions. Method: A systematic literature review was conducted, analyzing findings from 33 peer-reviewed studies across various educational contexts. The review examined both quantitative and qualitative evidence on the outcomes and perceptions of exit exams. Results: The review reveals that exit exams contribute positively to transparency, standardization, and alignment with labor market demands. They provide valuable feedback for curriculum development and institutional improvement. Conclusion: While exit exams have the potential to enhance graduate preparedness and institutional accountability, their current implementation often undermines equity and educational depth. A more balanced and inclusive approach is required to address these issues. Contribution: This review offers a comprehensive synthesis of the current discourse on exit exams and provides actionable insights for educators and policymakers. It advocates for integrating formative assessments, enhancing exam design, and prioritizing student well-being to create a more equitable and effective assessment framework in higher education.